Makna Ruang Ritual dan Upacara pada Interior Keraton Surakarta - Laksmi K. Wardani, Patricia Jessy Angelina (Intra, 2014)
The study of the meaning of ritual and ceremonial space is closely related to cultural studies which studied philosophy or meaning of a cultural object. a meaning is formed by symbols, human activities, cultures, and so on. Space in terms of the Java strongly associated with their understanding of the place. A place in the Javanese tradition is understood as a characteristic of daily activities. The aim of this study is to determine the physical reality of Surakarta Palace for ritual and ceremonial activities, as well as knowing the meaning of which is formed from the interaction between ritual and ceremony with the physical reality of Surakarta Palace, using a qualitative research method and field research strategy. This study is expected to help the author and other researchers to do a study about ritual and ceremonial space in Surakarta Palace. The result of this research is the knowledge about a space that is empty if there are no human activities in it. When the room is filled with activities, it has a meaning.